Global Existence and Blow-Up for the Euler-Bernoulli Plate Equation with Variable Coefficients - Jianghao Hao; Jie Lan (Journal of Function Spaces)
We prove the local existence, blow-up, global existence, and stability of solutions to the initial boundary value problem for Euler-Bernoulli plate equation with variable coefficients.